Serology surveillance of SARS-CoV-2 antibodies among healthcare workers in COVID-19 designated facilities in Malaysia - Yuan Liang Woon; Yee Leng Lee; Yoong Min Chong; Nor Aliya Ayub; Swarna Lata Krishnabahawan; June Fei Wen Lau; Ramani Subramaniam-Kalianan; I-Ching Sam; Yoke Fun Chan; Raj Kumar Sevalingam; Azura Ramli; Chuan Huan Chuah; et al. (Elsevier, 2021)
Background: Asymptomatic severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infections are well documented. Healthcare workers (HCW) are at increased risk of infection due to occupational exposure to infected patients. We aim to determine the prevalence of SARS-CoV-2 antibodies among HCW who did not come to medical attention. Methods: We prospectively recruited 400 HCW from the National Public Health Laboratory and two COVID-19 designated public hospitals in Klang Valley, Malaysia between 13/4/2020 and 12/5/2020. Quota sampling was used to ensure representativeness of HCW involved in direct and indirect patient care. All participants answered a self-administered questionnaire and blood samples were taken to test for SARS-CoV-2 antibodies by surrogate virus neutralization test. Findings: The study population comprised 154 (38.5%) nurses, 103 (25.8%) medical doctors, 47 (11.8%) laboratory technologists and others (23.9%). A majority (68.9%) reported exposure to SARS-CoV-2 in the past month within their respective workplaces. Adherence to personal protection equipment (PPE) guidelines and hand hygiene were good, ranging from 91-100% compliance. None (95% CI: 0, 0.0095) of the participants had SARS-CoV-2 antibodies detected, despite 182 (45.5%) reporting some symptoms one month prior to study recruitment. One hundred and fifteen (29%) of participants claimed to have had contact with known COVID-19 persons outside of their workplace. Interpretation: Zero seroprevalence among HCW suggests a low incidence of undiagnosed COVID-19 infection in our healthcare setting during the first local wave of SARS-CoV-2 infection. The occupational risk of SARS-CoV-2 transmission within healthcare facilities can be prevented by adherence to infection control measures and appropriate use of PPE.